Gifted education in Paraguay: analyses from a learning-resource perspective - Alexandra Vuyk; Maureen Montania; Liz Barrios; Montserrat Lobo (Cogent Education, 2024)
The objective of this study is to examine the educational experiences of gifted students in Paraguay through the lens of the Actiotope Model of Giftedness, which provides a comprehensive framework for analyzing the interplay between environmental and individual factors in the development of giftedness.In Paraguay, the approach to gifted education is guided by Law No. 5136/2013 on Inclusive Education, which focuses on providing tailored education to students with diverse cognitive abilities. The Ministry of Education and Sciences (MEC) further develops this approach in its Resolution 1188/2023, introducing specific strategies for supporting gifted students. These strategies include Curricular Enrichment, offering enriched learning experiences tailored to individual abilities, interests, and learning styles, and Flexible Promotion, allowing for the advancement of students through education based on their intellectual development and social maturity. Despite these efforts, national evaluations indicate a gap in achieving minimum educational standards, with only 4.4% of students demonstrating outstanding performance. The economic support for gifted education relies heavily on public and private contributions, often placing a significant financial burden on families. Furthermore, cultural misconceptions about giftedness, such as the belief that gifted children will succeed without additional support, and a lack of specialized training for educators pose ongoing challenges. Amidst these limitations, initiatives like educational robotics and participation in international competitions showcase areas where Paraguay’s gifted students excel. However, there is a clear need for a more structured financial approach and comprehensive educational strategies to enhance the support for gifted students.